The development and validation of a macronutrient and taste preference ranking task in multiethnic Asian population - Shua, Irving Yu Le (2024)
Understanding how changes in individual food preferences in a dynamic environment translate into dietary choices helps to unravel the aetiology of suboptimal nutrition in the population. To facilitate the measurements of food preferences in a multiethnic Asian population, we aimed to develop and validate the Macronutrient and Taste Preference Ranking Task (MTPRT) in an Asian population. We shortlisted 1770 local food items based on the predominant macronutrient groups (≥50 % macronutrient content is protein or fat or carbohydrates), classified their taste clusters, standard-photographed a final list of 36 food items, and developed an electronic survey through cognitive interviews with 30 participants. We then validated the MTPRT amongst 66 participants (mean (SD) age = 47.4 (11.7) years, 57.6 % male, with Chinese: Malay: Indian ethnicity ratio 3:1:1), through random crossover administration of sweet and savoury standard meals with equivalent macronutrients across 2 study visits over a week. The average duration taken to complete MTPRT was 14.1 (5.3) minutes. The sweet and savoury taste preference scores were inversely correlated (r = -0.9, p < 0.0001). The liking and preference for savoury taste were reduced after consuming savoury meals (p = 0.0009). The intra-person correlations for MTPRT scores were all r > 0.6, p < 0.001. The macronutrient preference scores were all positively associated with the self-reported macronutrient intakes derived from the Food Frequency Questionnaire, independent of sex, age, ethnicity, and BMI. Our study demonstrates the validity and reproducibility of MTPRT in multiethnic Asian populations for future evaluation of food preferences in multiethnic Asian population.